Nanotechnologies in the world crisis (Polis (Santiago), 2018)
The article discusses the development of nanotechnology in the context of the emergence of the global economic crisis. It starts by highlighting the key elements of a technological revolution: the technical characteristics, role in the accumulation of capital and the impact on social classes. After examining the place of technology in development, finally showing how the trends towards concentration of capital are involving nanotechnology, which can lead to a more unequal world than the one that exists today. Nanotechnology is the basis of the next industrial revolution which is already established. With the advent of the global economic crisis new technologies will also be impacted. Some government spokesmen have said that developed countries could be used as leverage to end the crisis, on the contrary in this article is stated the issue in the context of trends towards the concentration of capital.
Keywords: nanotechnology; economic crisis; capitalism